Challenges in Preform Material Preparation for Laser-Active Fibers - Wondraczek, Katrin; Müller, Robert; Reichel, Volker; Trautvetter, Tom; Wondraczek, Lothar (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
We present a novel approach in creating extremely uniform, actively doped core material for laser-active fibers produced by reactive powder-sintering (REPUSIL) or plasma enhanced deposition with dimensions around 15 mm x 100 mm or even larger.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Co-doping; Laser-active fibers; Optical fiber; Plasma enhanced deposition; Rare earth elements; REPUSIL